The gender aspect of the formation of values of physical training of students in higher education - Marchenko, O. Iu. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The analysis of the place of physical education in the hierarchy of values of university students. Addresses gender characteristics of the formation of values in physical education students. The study involved students in the amount of 419 people (206 boys, 213 girls) and first-year students (35 girls, 16 boys). The findings suggest that a combination of slightly traditionally masculine and feminine qualities in one person. It was found that in the study of gender differences in the choice of human traits observed distinct gender stereotypes. Among the young men identified the following personality traits: the ability to achieve goals by any means, physical strength, sociability, communication skills. Girls are the following traits: sociability, communication skills, good looks, intelligence and a wide range of interests, the ability to behave in public, optimism and prudence.